2012
DOI: 10.1177/0021998312446180
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy resin/polyetherimide/carbon black conductive polymer composites with a double percolation structure by reaction-induced phase separation

Abstract: A novel double-percolation structural conductive polymer composite based on epoxy/polyetherimide/carbon black was prepared for the first time. The electrical property, phase structure of the composite and the selective distribution of carbon black were investigated. The results show that a reaction-induced phase separation between epoxy and polyetherimide can be observed in epoxy/polyetherimide/carbon black composites. In the blend with 16 wt% polyetherimide, polyetherimide phase changes from a dispersed phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…suggested by Sumita et al [69] is widely and relatively successfully used to forecast distribution [32,49,60]. Wetting coefficient (ω a ) can be calculated according to equation 1:…”
Section: Prediction For Selective Distribution Of Gnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…suggested by Sumita et al [69] is widely and relatively successfully used to forecast distribution [32,49,60]. Wetting coefficient (ω a ) can be calculated according to equation 1:…”
Section: Prediction For Selective Distribution Of Gnpsmentioning
confidence: 99%
“…Another approach is the selective distribution of fillers in an immiscible polymer blend with a co-continuous structure [33,[47][48][49][50][51], a strategy that has also been applied in the design of electrically conductive composites [52][53][54][55]. For example, it has been found that silicon carbide will aggregate in a single polymer phase in an immiscible PS/PVDF blend to form an efficient thermally conductive network [33].…”
Section: Introductionmentioning
confidence: 99%
“…Some materials design approaches include the deposition of wire-like nanoconductors onto elastomeric substrates to form conducting grids. 15 Others involve incorporation of nanomaterials such as graphene, 16 carbon black, 17 metal nanowires, 18 or nanoparticles (NPs) 14,19,20 into elastic polymers. The interface between the nanoscale conductive elements and electroactive fluid outside of the electrode changes upon strain for all of these nanocomposites, because the nanoscale objects adjust their mutual orientation (self-assemble) under strain.…”
mentioning
confidence: 99%
“…Adding carbon nanotube, carbon black, graphite, graphene, and so on. into the insulating matrices is one of the conventional methodology [8][9][10][11][12]. Researchers have also studied conductive polymeric layer as an alternative option to provide safety against lightning strikes [13,14].…”
Section: Introductionmentioning
confidence: 99%